Noninvasive real-time monitoring of local drug release using nano-Au-absorbed self-decomposable SiO2 carriers. Issue 32 (2nd August 2018) - Fan, Li; Yang, Jingnan; Leung, Ken Cham-Fai; Song, Chaojun; Li, Quan
Abstract : In the present work, we demonstrated for the first time in a mice bearing Colo-205 xenograft model system that local drug release at the tumor site can be tracked in real time via the establishment of a quantitative correlation between the drug release and a specific imaging agent for CT. Abstract : Real time monitoring of drug release at specific local sites by a non-invasive imaging method is critical in patient-specific drug administration in order to avoid insufficient or excess drug dosing. In the present work, we designed a specific carrier system for such a purpose using self-decomposable SiO2 nanoparticles (NPs) with the drug being loaded in the center and Au NPs on the SiO2 NPs as the imaging agent. We discovered a correlation between the drug release from the carrier and the morphological evolution of Au NPs, which also left the carrier and changed their aggregation states along with the drug release process. This finding enabled the real time monitoring of the drug release at local sites ( e.g. tumor) in a quantitative manner by recording the CT signal evolution of the Au NPs, as demonstrated in vivo using mice bearing Colo-205 xenografts. The present work provided a promising platform for non-invasive real time tracking on the localized drug release, enabling a variety of personalized therapeutic applications.